Disparität von Attribuierungen in polnischen und deutschen Adjektiv-Substantiv-Kollokationen als Translationsproblem - Żmudzki, Jerzy (Glottodidactica, 1999)
The aim of this paper is to show what sort of translation problems appear in the adjective-substantive collocations in Polish and German. A special class of collocations is represented by lexicalised and idiomatised syntagmas. These units include characteristic attributive perspectives specified by the two languages and the two culture communities. This phenomeneon refers to conventional valuing, attributions and métaphorisations of concepts represented in substantives used. In this way collocations form and fix the cultural profiles of reality. Because of that they can be regarded as cognitive formulas which need to be reprofiled in a concrete translation process through their projection on the target language and culture. As a result of these cognitive and linguistic operations the translator identifies the convergences and divergences as determined by the language system and the text between both the two languages. He secondly constructs equivalent attributive profile of the concept transferred into the target text, thus guaranteeing the reciprocity of perspectives between both of the texts. The essay classifies the cases and types of disparities between Polish and German adjeck-tive-substantive collocations, showing how they can be reprofiled according to linguistic and cultural requirements of the target text. This class of translation problems is only a subfield of the larger domain, but the main mechanism of the important translation transfer can be already demonstrated and exemplified basing on these specific translation units.